Employment Generation in Rural Africa : Mid-Term Results from an Experimental Evaluation of the Youth Opportunities Program in Northern Uganda - Blattman, Christopher; Fiala, Nathan; Martinez, Sebastian (World Bank, Washington, DC, 2017)
Can cash transfers promote employment and reduce poverty in rural Africa? Will lower youth unemployment and poverty reduce the risk of social instability? The authors experimentally evaluate one of Uganda's largest development programs, which provided thousands of young people nearly unconditional, unsupervised cash transfers to pay for vocational training, tools, and business start-up costs. Mid-term results after two years suggest four main findings. First, despite a lack of central monitoring and accountability, most youth invest the transfer in vocational skills and tools. Second, the economic impacts of the transfer are large: hours of non-household employment double and cash earnings increase by nearly 50 percent relative to the control group. The authors estimate the transfer yields a real annual return on capital of 35 percent on average. Third, the evidence suggests that poor access to credit is a major reason youth cannot start these vocations in the absence of aid. Much of the heterogeneity in impacts is unexplained, however, and is unrelated to conventional economic measures of ability, suggesting we have much to learn about the determinants of entrepreneurship. Finally, these economic gains result in modest improvements in social stability. Measures of social cohesion and community support improve mildly, by roughly 5 to 10 percent, especially among males, most likely because the youth becomes a net giver rather than a net taker in his kin and community network. Most strikingly, we see a 50 percent fall in interpersonal aggression and disputes among males, but a 50 percent increase among females. Neither change seems related to economic performance nor does social cohesion a puzzle to be explored in the next phase of the study. These results suggest that increasing access to credit and capital could stimulate employment growth in rural Africa. In particular, unconditional and unsupervised cash transfers may be a more effective and cost-efficient forming of large-scale aid than commonly believed. A second stage of data collection in 2012 will collect longitudinal economic impacts, additional data on political violence and behavior, and explore alternative theoretical mechanisms.